(untitled) - Kuther, Tara L.; Tara L. Kuther (Australia,Belmont, CA)
This handbook, by Tara L. Kuther, offers undergraduate students the information they need to make informed decisions about whether to pursue psychology as a major and career, as well as succeed in their psychology course. The first chapter introduces students to the scope of psychology and the subspecialties within psychology. Subsequent chapters help students assess their skills, abilities, and interests. Career opportunities at the undergraduate and graduate levels are presented so students can decide whether psychology is an appropriate major for them. Available at a discounted price when packaged with the text; contact your Wadsworth Cengage Learning representative for more information
Includes bibliographical references (p. 228-234) and index
Keywords: Psychology; Psychology; Psychology; Applied